Doing and using educational research: collaborative approaches in changing contexts. (November 2016) - Moore, Alex
This paper suggests that, while continuing to critically address abiding issues concerning the nature and purposes of mass education, educational research needs to embrace new contexts and emphases as we move deeper into the 21st century. These contexts and emphases – in particular those related to globalization in its various forms, and to rapid developments in digital technologies – require new approaches to how, and perhaps by whom, educational research is undertaken. Such approaches might involve 'pooling' knowledge and understandings in arriving at more nuanced and thorough understandings of learning, society and human development – breaking down or weakening, in the process, existing barriers both between traditional research disciplines and between research and its implementation: in particular, challenging existing identifications of those who 'do' educational research and those who might make use of it. Referencing Guattari's notion of the 'group subject', it is argued that such changed relationships within research-and-practice communities must be accompanied by parallel changes in the relationships between central education policy and research, resulting in more collaborative approaches to policy formation.